The predictive value of suPAR for glomerular segmental sclerosis lesions in renal pathology - Zurong Zhang; Chongbin Liu; Yachun Han; Daming Li; Yao Huang; Kewen Shi; Shiyu Xia; Jinying Wei; Hong Liu; Lin Sun; Xuejing Zhu; Shuguang Yuan (Renal Failure)
Introduction Soluble urokinase-type plasminogen activator receptor (suPAR) is a potential circulating pathogenic factor in idiopathic focal segmental glomerulosclerosis (iFSGS); however, its role remains controversial. Glomerular segmental sclerosis lesions (S lesions) are commonly observed in IgA nephropathy (IgAN). This study aims to investigate the correlation between suPAR and S lesions, particularly in IgAN, and to evaluate the potential of suPAR as a prognostic marker.Methods Patients were selected from the Second Xiangya Hospital, including 47 cases of IgAN with S lesions (IgAN(S1 group)), 13 cases of IgAN without S lesions (IgAN(S0 group)), and 13 cases of iFSGS. Healthy control group of 20 individuals was selected. Serum suPAR concentration was measured, and its correlation with clinical and pathological data was analyzed. Patients were followed to evaluate the prognostic value of suPAR.Results Compared to the healthy control group and IgAN (S0 group), patients in the iFSGS and IgAN (S1 group) had significantly higher serum suPAR concentration (p < 0.05). In IgAN patients, serum suPAR concentration was negatively correlated with eGFR (r = −0.458, p < 0.05) and positively correlated with the presence and proportion of S lesions (r = 0.448, p < 0.001; r = 0.435, p < 0.05). The incidence of composite kidney endpoint events was significantly higher in IgAN patients with high baseline serum suPAR concentration than in those with low level of suPAR (p < 0.05).Conclusions High serum suPAR concentration is a predictor of S lesions in the kidney and a risk factor for poor prognosis, making it a potential therapeutic target and prognostic predictor for kidney disease.